PELAKSANAAN PROMOSI PADA EVENT WISATA BAKAR TONGKANG - Maharani, Siti; Sidiq, RD.SITI Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This thesis discusses the implementation of promotions at the barge burning tourism event in Rokan Hilir Regency. This research was conducted on Jl, Bintang No. 99 Bagan Punak Pesisir, Bagan Siapi-api, Rokan Hilir Regency, specifically the Bakar Barge tourist event, in this case it was motivated by problems that arose in the event implementation activities and promotional systems or discussing the problem of how the promotion strategy was carried out by the Youth and Sports Tourism Office. This research aims to find out how promotions are carried out by the management and what obstacles the management faces in promoting the barge burning tourism event. This research uses a qualitative method with a descriptive approach. This researcher used interview, observation and documentation techniques. The results of this research show that in implementing the Bakar Tongkang tourism event, 5 promotional mixes have been implemented, including advertising, sales, personal selling, public relations and direct marketing. Keywords: Strategy, Promotion , Tourist Event